Implementation of Classroom Management To Improve Students Academic Achievement In The Subject of Islamic Religious Education (A Case Study at SD Al Kenzie Bandung) - Dian, Dian; Dantika, Fina Azizah; Kamaludin, Kamaludin; Anwar, Miftahul; Marlina, Lenny; Ariatpi, Fina (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
Management is the specialized skill possessed by an individual to carry out activities independently, collectively, or through others to achieve organizational goals in a productive, effective, and efficient manner. The objectives of this research are (1) to plan a learning system to improve students' academic achievement at Al Kenzie Elementary School, (2) to design a learning system to enhance students' academic achievement at Al Kenzie Elementary School, and (3) to implement classroom management to improve students' learning achievement at Al Kenzie Elementary School. This research uses a qualitative descriptive method, and the research population consists of three respondents: the school principal, class teachers, and students. Data collection techniques include observation, interviews, and documentation. Based on the research results, (1) the classroom design plan implemented by teachers at Al Kenzie Elementary School in the subject of Islamic religious education involves designing the classroom as a learning environment, providing and organizing facilities and learning support media, and developing and teaching according to the social, economic, cultural needs, and characteristics of different students. (2) The implementation of classroom arrangement at Al Kenzie Elementary School includes spatial arrangement, seating arrangement, effective teaching methods, and the use of supportive media. (3) The implementation of classroom management at Al Kenzie Elementary School involves creating a harmonious and communicative interaction atmosphere in the subject of Islamic religious education.